(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
The article discusses the structure of the etymological dictionary, the etymological interpretation of synonyms and homonyms belonging to its own layer of the Uzbek language, and the possibilities of processing them as a semantic extension. The author of the dictionary states that in the etymological interpretation of the words in the modern Uzbek literary language by sound, this characteristic of the vowels of the ancient Turkic language in terms of hardness and softness has partially preserved its power in some dialects of the Uzbek language. is not taken into account in the literary language.